Natural variation of CTB5 confers cold adaptation in plateau japonica rice - Haifeng Guo; Shilei Gao; Huahui Li; Jiazhen Yang; Jin Li; Yunsong Gu; Qijin Lou; Runbin Su; Wei Ye; Andong Zou; Yulong Wang; Xingming Sun; et al. (Nature Communications)
Abstract During cold acclimation in high-latitude and high-altitude regions, japonica rice develops enhanced cold tolerance, but the underlying genetic basis remains unclear. Here, we identify CTB5, a homeodomain-leucine zipper (HD-Zip) transcription factor that confers cold tolerance at the booting stage in japonica rice. Four natural variations in the promoter and coding regions enhance cold response and transcriptional regulatory activity, enabling the favorable CTB5 KM allele to improve cold tolerance. CTB5 interacts with OsHox12 and targets gibberellin (GA) metabolism genes to promote GAs accumulation in anthers and facilitate tapetum development under cold stress. Moreover, CTB5 directly regulates PYL9 and improves cold tolerance at the seedling stage by reducing reactive oxygen species (ROS) accumulation. The CTB5 KM allele is selected during the cold acclimation of japonica rice to plateau habitats in Yunnan Province. Our findings provide insights into the mechanisms underlying cold adaptation in plateau japonica rice and offer potential targets for breeding cold-tolerant rice varieties.